Scintillation characteristics of deformed large-sized NaI crystals - Shlyakhturov, V.V.; Gektin, A.V.; Boyarintsev, A.Yu.; Taranyuk, V.I. (Functional Materials, 2013)
The effect of plastic deformation on defect structure and functional parameters of NaI based crystals and scintillator NaI(Tl) in particular has been studied. Plastic flow modeling in decorated samples as well as in large size crystal blanks demonstrated significant non uniformity of the deformation map along the sample. Scintillation parameters (light output and energy resolution) are practically the same through the whole crystal volume. Post deformation scintillation parameters are similar to the single crystal ones. This phenomenon is typical for the wide range of temperature and deformation rates for this type of crystals.